Lobar intracerebral hemorrhage and risk of subsequent uncontrolled blood pressure. (September 2022) - Myserlis, Evangelos Pavlos; Mayerhofer, Ernst; Abramson, Jessica R; Teo, Kay-Cheong; Montgomery, Bailey E.; Sugita, Lansing; Warren, Andrew D; Goldstein, Joshua N; Gurol, Mahmut Edip; Viswanathan, Anand; Greenberg, Steven M; Biffi, Alessandro; et al.
Background: Uncontrolled blood pressure (BP) in intracerebral hemorrhage (ICH) survivors is common and associated with adverse clinical outcomes. We investigated whether characteristics of the ICH itself were associated with uncontrolled BP at follow-up. Methods: Subjects were consecutive patients aged ⩾18 years with primary ICH enrolled in the prospective longitudinal ICH study at Massachusetts General Hospital between 1994 and 2015. We assessed the prevalence of uncontrolled BP (mean BP ⩾140/90 mmHg) 6 months after index event. We used multivariable logistic regression models to assess the effect of hematoma location, volume, and event year on uncontrolled BP. Results: Among 1492 survivors, ICH was lobar in 624 (42%), deep in 749 (50%), cerebellar in 119 (8%). Lobar ICH location was associated with increased risk for uncontrolled BP after 6 months (OR 1.35; 95% CI [1.08–1.69]). On average, lobar ICH survivors were treated with fewer antihypertensive drugs compared to the rest of the cohort: 2.1 ± 1.1 vs 2.5 ± 1.2 ( p  < 0.001) at baseline and 1.8 ± 1.2 vs. 2.4 ± 1.2 ( p  < 0.001) after 6 months follow-up. After adjustment for the number of antihypertensive drugs prescribed, the association of lobar ICH location with risk of uncontrolled BP was eliminated. Conclusions: ICH survivors with lobar hemorrhage were more likely to have uncontrolled BP after 6 months follow-up. This appears to be a result of being prescribed fewer antihypertensive medications. Future treatment strategies should focus on aggressive BP control after ICH independent of hemorrhage location. Graphical abstract